Guaranteeing lesbian, gay, bisexual and transgender (LGBT) people’s rights : a responsibility for Europe’s towns and regions : debated and adopted by the Council of Europe Congress of Local and Regional Authorities on 25 March 2015 - Renström, Yoomi (S.l.: Council of Europe, 2015)
"Fonds Suzan Daniel (FSD)"